Region of Murcia's 2022 report card on physical activity for children and youth - José Francisco López-Gil; Pilar Sainz de Baranda; Noelia González-Gálvez; Eduardo Segarra-Vicens; Alfonso Valero-Valenzuela; Antonio Avellaneda; María Alegría Avilés-Martínez; Sergio López Barrancos; Miguel Díaz Delgado; Desirée Victoria-Montesinos; Fernando Ureña Villanueva; Pedro Emilio Alcaraz (Elsevier, 2024)
Objective: The aim of this review was to summarize the process and results of the Region of Murcia's 2022 Report Card on Physical Activity for Children and Youth. Methods: Indicators from the Global Matrix initiative (Overall Physical Activity, Organized Sport & Physical Activity, Physical Fitness, Active Play, Active Transport, Sedentary Behaviors, Family & Peers, School, Community & Environment, and Government) were evaluated based on the best available data in the Region of Murcia. Results: Active play was the indicator with the highest grade (B+), followed by Organized Sport & Physical Activity (B) and Active Play (B). School and Family and Peers indicators obtained a C+ and C grade, respectively. Both Community and Environment and Sedentary Behaviors indicators received a D+ grade. The grade for Overall Physical Activity and Government indicators was D. Physical Fitness was the indicator with the lowest grade of this Report Card (D−). None of the indicators received an incomplete grade (INC) because of a lack of available information. Conclusions: The present Report Card offers evidence highlighting the low level of physical activity in Spanish children and adolescents living in the Region of Murcia. Further studies and surveillance efforts are urgently needed for most of the indicators analyzed, which should be addressed by researchers and the Region of Murcia's Government for this specific population. A strong commitment from the Government of the Region of Murcia is needed at all levels to promote a cultural change that will lead children and young people in this region to improve the current situation.